A treasury of five-minute stories - "Waters, Fiona" (Kingfisher: London, 2000)
There's always time for a story ... From a big bear who loves hugs to a little worm who longs to glow - here are over twenty stories from some of today's favourite authors. Perfect for reading aloud, every tale here has the power to entertain and delight a child in just five minutes. This varied collection proves even the shortest stories can be a special time!
Keywords: Children's stories, English